Sob a ótica do projeto: o arquiteto Eduardo Mendes Guimarães Junior e a reitoria da UFMG - Masini, Daniele Forlani (2015)
This research deals with a study of the theoretical and projective reflections of modern mining architect Eduardo Mendes Guimarães Junior. Architect, teacher, editorialist, technical director of a major magazine and chairman of the Institute of Architects of Brazil - Department Minas Gerais (IAB -MG), Guimarães staked its presence in the history of architecture in Minas Gerais, through a theoretical discussion present in various texts published and architectural production of important buildings constructed in the city of Belo Horizonte. Despite its great relevance in the architectural scene of Belo Horizonte in the 1950s and 1960s, there are few studies referenced on the architect, which reinforces the need for a bailout this not so distant memory. Therefore, the aim of this dissertation is to analyze the theoretical and architectural production of Eduardo Mendes Guimarães Junior, analyzing one of his most iconic buildings and consistently projects maturity, the Rectory of the Federal University of Minas Gerais, using his own speech. For a better understanding of the importance of this work and its insertion into the Brazilian modern architecture, two other similar character works were chosen to be compared, the building of the School of Engineering of São Carlos, project of Hélio de Queiroz Duarte Architect and Ernest Robert engineer Carvalho Mange, and the building of the School of Architecture of the University of Brazil (now Federal University of Rio de Janeiro - UFRJ), project of Jorge Machado Moreira .